2022
DOI: 10.1155/2022/9089365
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol Extract of YFXJ Decoction Reverses the Drug Resistance of Human Lung Adenocarcinoma Cell Line A549/DDP

Abstract: Objective. Lung cancer is the wide and common tumor. This study was designed to explore the effect of YFXJ formula on non-small-cell lung cancer (NSCLC) cell lines. Methods. YFXJ formula (mainly composed of Astragalus membranaceus, Atractylodes macrocephala, Radix Saposhnikoviae, Radix Glehniae, coix seed, Herba Sabina chinensis, Hedyotis diffusa, Pericarpium Citri Reticulatae, sarcophagus martensii, Prunella vulgaris, Meretrix meretrix, and oyster) was extracted with 75% ethanol. We performed MTT, FACS, TUNEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%